Contribution of Tarbawi Tafsir in Increasing the Competency of Religious Education Teachers: Study of Tafsir Surah Luqman Verse 12 - Guntur Rijaludin; Iskandar Mirza (Classroom: Journal of Islamic Education, 2025)
Tafsir Tarbawi is an approach to interpreting the Qur'an that prioritizes educational values and character formation through moral and spiritual messages in the verses of the Qur'an. This research aims to analyze the contribution of Tafsir Tarbawi, especially in Surah Luqman Verse 12, to increasing the competence of Islamic Religious Education (PAI) teachers. Teachers' competencies, which include pedagogical, personality, social, and professional aspects, are key to creating quality religious education. This verse highlights the importance of wisdom and gratitude, which can be used as a guide to educate students to have good character, discipline and responsibility. Through a descriptive qualitative approach, this research identifies that Tafsir Tarbawi is not only relevant to deepen understanding of the Qur'an but also provides practical guidance for teachers in integrating Islamic values into learning curricula. The research results show that the application of Tarbawi Tafsir in learning can improve the quality of teaching, encourage teachers to be good role models, and help students understand and apply Islamic values in everyday life. However, the study also found several obstacles, such as minimal resources and a curriculum that did not fully support this approach. With the right training and support, Tafsir Tarbawi has the potential to become a strategic solution to increase teachers' professional competence while forming a generation with an Islamic character.